The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1103/physrevlett.120.025002
|View full text |Cite|
|
Sign up to set email alerts
|

Measurement of Preheat Due to Nonlocal Electron Transport in Warm Dense Matter

Abstract: This Letter presents a novel approach to study electron transport in warm dense matter. It also includes the first x-ray Thomson scattering (XRTS) measurement from low-density CH foams compressed by a strong laser-driven shock at the OMEGA laser facility. The XRTS measurement is combined with velocity interferometry (VISAR) and optical pyrometry (SOP) providing a robust measurement of thermodynamic conditions in the shock. Evidence of significant preheat contributing to elevated temperatures reaching 17.5-35 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Figure 3 shows the temperature profile of 3 separate simulations at 2 ns with a 1, 5, and 10 eV preheat. The 10 eV preheat (larger than expected from past studies [5]), produces only a small (∼ 1 − 2 eV) difference in the profile temperature. Our analysis supports the practice in most radiation transport experiments that this heating is unimportant because both the amount of high-energy emission (electrons and photons) is small compared to the total emission and most of this emission streams through the target.…”
Section: Drivementioning
confidence: 54%
See 1 more Smart Citation
“…Figure 3 shows the temperature profile of 3 separate simulations at 2 ns with a 1, 5, and 10 eV preheat. The 10 eV preheat (larger than expected from past studies [5]), produces only a small (∼ 1 − 2 eV) difference in the profile temperature. Our analysis supports the practice in most radiation transport experiments that this heating is unimportant because both the amount of high-energy emission (electrons and photons) is small compared to the total emission and most of this emission streams through the target.…”
Section: Drivementioning
confidence: 54%
“…Non-thermal electrons produced in the hohlraum can stream into the target, preheating the target material prior to the launch of the radiation front. For low-drive experiments, a few eV pre-heat can alter the evolution of the shock front [5]. But, for the COAX experiment, even a 10 eV pre-heat does not significantly alter the flow of the much more powerful COAX drive.…”
Section: Drivementioning
confidence: 98%
“…Theimportance of thenonlocal electron transport has been recently observed experimentally, where it was demonstrated that theclassical diffusive hydrodynamics fails to model thereal behavior of the plasma. In contrast, theNTH model succeeds to predict acomplex plasma behavior [12].…”
Section: Nth Model Of Laser-heated Plasmamentioning
confidence: 84%
“…The plasma profile and the temperature are strongly affected by these nonlocal processes[7], which may also lead to asignificant effect on thehigh-power laser interaction as demonstrated in this work. A correct treatment of the ablation process requires anaccurate nonlocal radiation-hydrodynamics, which has been demonstrated in[8][9][10][11][12] during last several decades.Ablation physics under nonlocal transport conditions is of importance for two main applications:…”
mentioning
confidence: 99%
“…In dense plasmas, DSF, usually probed in x-ray Thomson scattering experiments, is considered as an important, and sometimes irreplaceable, diagnostic tool to probe thermal properties, such as temperature and density, in the internal regime of dense plasmas. [5,[38][39][40][41][42] It is a common practice to calculate DSF in the framework of time-dependent density functional theory (TDDFT), [43,44] which avoids the cumbersome calculation of the Bethe-Salpeter equation [1,45] of the many-body perturbation theory (MBPT) approach, owing to the less important contribution of long-range exchange and correlation effect in the DSF. [1] It was shown [16,25,35,46,47] as a rule of the thumb that for |𝑞| smaller than twice of the plasmon cutoff wave vector 𝑞c, the method reproduced the experimental DSF well with lifetime broadening effects included semi-empirically.…”
mentioning
confidence: 99%